Enhancing Input On and Above the Interactive Surface with Muscle Sensing - Benko, Hrvoje; Saponas, Scott; Morris, Dan; Tan, Desney (ITS '09 Proceedings of the ACM International Conference on Interactive Tabletops and Surfaces, 2009)
Current interactive surfaces provide little or no information about which fingers are touching the surface, the amount of pressure exerted, or gestures that occur when not in contact with the surface. These limitations constrain the interaction vocabulary available to interactive surface systems. In our work, we extend the surface interaction space by using muscle sensing to provide complementary information about finger movement and posture. In this paper, we describe a novel system that combines muscle sensing with a multi-touch tabletop, and introduce a series of new interaction techniques enabled by this combination. We present observations from an initial system evaluation and discuss the limitations and challenges of utilizing muscle sensing for tabletop applications.